Sistem Prediksi Kebutuhan Obat di Puskesmas Menggunakan Metode Least Square - Devit Suwardiyanto; Mohammad Nur Shodiq; Dedy Hidayat Kusuma; Tovia Oktalita Sari (Politeknik Harapan Bersama, 2019)
The Puskesmas is a health service center at the first level in the community. Medication is an important requirement in health agencies, including health centers. The Puskesmas must provide medicine for patients for a period of a month. As well, the puskesmas also has to plan drug requests for the period of the following month. The problem that often arises is about drug supplies. If the demand for drugs is too much, it will cause the drug to be removed for a long period of time, so that it will result in drug expiration. Likewise, if the demand for drugs is too little then it becomes less good, which results in less optimal service to the community. During this time, planning for drug demand for use in the next period, still using instinctive techniques by the head of the health center of the puskesmas. So, this will lead to excess or even reduced drug supply. In this study a system that is able to predict future drug needs was built. The results of this prediction can be used as a reference for drug requests to the health department. The method used to predict is the Least Square method, while the system to control the upper and lower limits uses the Minimum Maximum Stock Level (MMSL) method. The test system for prediction errors in this study uses Mean Absolute Percentage Error (MAPE). This systems was implemented using the PHP language and visualized on a web-based basis. The system test results showed an average prediction error rate of 12.70%. The existence of this system is expected to be able to assist the planning process of drug needs in the future at the puskesmas.